Reputation and corporate strategy: A review of recent theory and applications - Weigelt, Keith; Camerer, Colin (Strategic Management Journal, 1988)
Abstract A corporate reputation is a set of attributes ascribed to a firm, inferred from the firm's past actions. While the intuition behind reputation‐building is hardly new, recent research has formalized the concept. We review this research and then, using examples, illustrate some of the strategic behavioral implications of these formal models.